Estudio de factibilidad para la creación de una planta desamargadora de chocho (lupinus mutabilis sweet) en el barrio Chan, parroquia Eloy Alfaro, cantón Latacunga, provincia de Cotopaxi en el período 2014-2015 - Ruiz Rocha, Luis Antonio (2016)
The present research work is intended to determine “THE FEASIBILITY FOR THE CREATION OF A PLANT WHICH TAKES OFF THE BITTER FLAVOR FROM “CHOCHO” AT NEIGHBORHOOD CHAN, PARISH ELOY ALFARO, LATACUNGA CANTON, and COTOPAXI PROVINCE 2014-2015” In the market study, there were some favorable results obtained for the project, since a demand of 1´064.575kg and an offer of 337.272kg annual chochos determined, leaving an unmet demand 727.303kg / year, which will consider our market niche, to try to satisfy a percentage of that demand with production to be performed in the new plant. Within the Technical Study, it was determined the investment and costs that will have each of the factors to create the plant, by giving a total investment of US $ 78.254,00, necessary for the creation of the plant.